Short-Term Prognostic Factors in Hospitalized Herpes Zoster Patients and Its Associated Cerebro-Cardiovascular Events: A Nationwide Retrospective Cohort in Japan - Ishikawa, Yuichi; Nakano, Kazuhisa; Tokutsu, Kei; Nakayamada, Shingo; Matsuda, Shinya; Fushimi, Kiyohide; Tanaka, Yoshiya (Frontiers in Medicine, 2022)
Background: Short-term mortality and incidence of cerebrovascular and cardiovascular events (C-CVE) during hospitalization of patients with severe herpes zoster (HZ) have not been sufficiently investigated. We aimed to investigate short-term prognosis and incidence of C-CVE associated with HZ in hospitalized patients. Methods: This retrospective cohort study from April 2016 to March 2018 included HZ inpatient cases selected from the Diagnosis Procedure Combination database—a Japanese nationwide inpatient database. HZ and C-CVE were diagnosed based on the 10th revision of the International Classification of Diseases and Injuries codes. The definition of primary exposure was that treatments were initiated within 7 days of admission, and antivirals were administered for ≥7 days. The main Outcomes were in-hospital deaths and C-CVE onset after hospitalization. Results: Among 16,811,501 in-hospital cases registered from 1,208 hospitals, 29,054 patients with HZ were enrolled. The median age was 71.0 years, 15,202 cases (52.3%) were female, and the HZ types were the central nervous system (n=9,034), disseminated (n=3,051), and ophthalmicus (n=1,069) types. There were 301 (1.0%) in-hospital deaths and 385 (1.3%) post-hospitalization onset of C-CVE. The 30-day in-hospital survival rates with or without underlying disease were 96.8% and 98.5%, respectively. Age ≥75 years (hazard ratio [HR], 2.18; 95% confidence interval [CI], 1.55–3.05), liver cirrhosis or hepatic failure (HR, 5.93; 95% CI, 2.16–16.27), chronic kidney disease (HR, 1.82; 95% CI, 1.24–2.68), heart failure (HR, 1.65; 95% CI, 1.22–2.24), and old cerebrovascular events (HR, 1.92; 95% CI, 1.10–3.34) were associated with poor short-term prognosis. Age ≥75 years (odds ratio [OR], 1.70; 95% CI, 1.29–2.24), diabetes (OR, 1.50; 95% CI, 1.19–1.89), dyslipidemia (OR, 1.95; 95% CI, 1.51–2.51), hyperuricemia (OR, 1.63; 95% CI, 1.18–2.27), hypertension (OR, 1.76; 95% CI, 1.40–2.20), heart failure (OR, 1.84; 95% CI, 1.32–2.55), and glucocorticoid administration (OR, 1.59; 95% CI, 1.25–2.01) were associated with increased risks for in-hospital C-CVE onset. Conclusions: The underlying diseases that could influence the short-term mortality of severe HZ were identified. Glucocorticoid is a possible risk factor for the in-hospital onset of C-CVE after severe HZ development.